Cultura organizacional y satisfacción laboral de los trabajadores en la empresa agroindustrial danper arequipa sac - 2012 - Neira Ramirez, Teresa De Jesús (2013)
This thesis was carried out with the purpose to analyze the influence of organizational culture on the job satisfaction of workers of the agroindustrial company DANPER Arequipa Sac. It has been considered the type of applied research, on the basis of an explanatory design, and the sample consisted of 158 workers, with whom they work by applying the methods and techniques of quantitative and qualitative research. The conclusion drawn from the results is that there is a deficient organizational culture and is generating problems in the job satisfaction of workers. This situation has been reflected in the lack of identity, the lack of implementation of the corporate values, mistrust, adverse working conditions and the lack of labor commitment that affects corporate profitability. Finally it is recommended that you implement labor market policies with projection of socio-economic measures and technical - organizational to improve working conditions and wrangle a job satisfaction that positive impact on the level of production and productivity of this agro-industrial company.